Opportunities and challenges of knowledge management on Electronic Platform for Adult Learning in Europe - Poceviciene, Rasa; Stasenaite, Violeta; Jakutiene, Rita (Encontros da Licenciatura em Ciências e Tecnologias da Documentação e Informação, 2022)
Knowledge and their management are vitally important for all firms and organizations in the contemporary world. The ability to create, acquire, integrate, deploy distributed knowledge is fundamental organizational capability. For successful functioning firms and organizations must not only exploit already existing knowledge, but must also invest into permanent exploring and creating new knowledge as strategic options for future development and competitive advantage. In this case the knowledge systems especially specialized are very important and useful. Of course, such knowledge systems create a lot of opportunities for users but at the same time raise some challenges and problems also (for example, lack or limits of knowledge managing, information seeking, self-directed learning and other skills). In this presentation opportunities and challenges of such knowledge management are analyzed on the bases of the Electronic Platform for Adult Learning in Europe (“Epale”). The exceptional feature of this platform is that active users can not only use the information, but also create or reconstruct, in other words, manage, the content of the platform also Aim of the platform is to become the main reference point for adult learning professionals in Europe. It offers a place to meet and discuss important adult learning topics, as well as to exchange ideas and materials to support professional practice. This type of community platform is the first of its kind for the sector of adult learning, especially non-formal. The research deal with the main aspects of the development of knowledge and e-learning management system in an institution or organization based on content analysis of scientific sources, documents and analysis of empirical data. knowledge management, ,